First measurement of the |𝑡| dependence of incoherent 𝐽/𝜓 photonuclear production - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kroesen, Martin; Nath, Abhishek; et al. (Physical review letters, 2024)
The first measurement of the cross section for incoherent photonuclear production of 𝐽/𝜓 vector mesons as a function of the Mandelstam |𝑡| variable is presented. The measurement was carried out with the ALICE detector at midrapidity, |𝑦| <0.8, using ultraperipheral collisions of Pb nuclei at a center-of-mass energy per nucleon pair of √𝑠NN=5.02 TeV. This rapidity interval corresponds to a Bjorken-𝑥 range (0.3-1.4)×10−3. Cross sections are given in five |𝑡| intervals in the range 0.04<|𝑡|<1 GeV2 and compared to the predictions by different models. Models that ignore quantum fluctuations of the gluon density in the colliding hadron predict a |𝑡| dependence of the cross section much steeper than in data. The inclusion of such fluctuations in the same models provides a better description of the data.
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, J. Crkovská, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, J.J. Seo, G. Skorodumovs, J. Stachel, S. Stiefelmeier, C.A. van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone [und viele weitere]
Gesehen am 19.05.2025